A MODEL FOR STRENGTH AND DEFORMATION CALCULATION OF SAW-BLADE FRAME WITH TAKING INTO ACCOUNT THE COMPRESSION OF THE VERTICAL FRAME’S STANDS (Innovation in Woodworking Industry and Engineering design, 2026)
In traditional textbooks in woodworking machines, a model is suggested for strength and deformation calculation of a saw-blade frame which is superfluously simplified: each of the two beams of the frame is considered as a simple one on two articulated supports that are swivels of the vertical frame’s stands. However, the joints between the beams and the stands are not articulated but rigid. Therefore, the saw-blade frame should be definitely considered namely as a frame with rigid joints. In the textbooks in Strength of Materials, there is a classi-cal theme about solving internally statically indeterminate closed frame with rigid joints. The author has always stated while teaching and writing textbooks that the saw-blade frame is a very suitable example to the classical theme mentioned. In the first author’s textbook in Strength of Materials, the solution of the statically indeterminate scheme of a similar frame has been demonstrated based on the strain-energy methods. Following the classical manner, the internal bending moment has only been envisaged while the strain energy is composed. A corresponding calculation scheme has been created and adopted in a book of Professor Obreshkov. Now, a more precise calculation model is proposed taking also into account the compression of the stands while the strain energy is formed. Correspondingly, deformational shortening the stands is involved. Besides the solutions of the statically indeterminate problem, an equation has been deduced for the deformational shortening the distance between the mean cross sections of the two beams. The paper throws light on the question of how well-grounded the simplification is to consider each of the two beams as a simple one on two articulated supports.